SAM 2 measurements of the polar stratospheric aerosol, volume 8 - Brandl, D.; Mccormick, M. P. (1986)
The Stratospheric Aerosol Measurement (SAM) 2 sensor aboard Nimbus 7 is providing extinction measurements of Antarctic and Arctic stratospheric aerosols with a vertical resolution of 1 km. Representative examples and weekly averages including corresponding temperature profiles provided by NOAA for the time and place of each SAM 2 measurement (Apr. 1982 - Oct. 1982) are presented. Contours of aerosol extinction as a function of altitude and longitude or time are plotted, and aerosol optical depths are calculated for each week. Typical values of aerosol extinction at 1.0 microns in the main stratospheric aerosol layer are approximately 4 to 6 times .0001/km at the beginning to 1 to 2 times .001/km at the end of the time period for the Antarctic region and approximately 1 to 3 times .001/km for the Arctic region throughout the time period. Stratospheric optical depths are about 0.002 to 0.009 for the Antarctic region and about 0.007 at the beginning to 0.024 at the end of the time period for the Arctic region. Polar stratospheric clouds were observed during the Antarctic winter, as expected. This report provides, in a ready-to-use format, a representative sample of the eighth 6 months of data to be used in atmospheric and climatic studies.